AI-Driven Quality Management and Digital Transformation in Islamic Education: A Systematic Review - Hamdi; Muhammad Lanri Siregar; Efrita Norman (Al-Qalam Institue, 2026)
This study aims to synthesize existing research on artificial intelligence (AI) enabled quality management and digital transformation in education and to examine their implications for Islamic education. A systematic literature review (SLR) was conducted using Scopus as the primary database. Relevant publications were identified through keywords related to artificial intelligence, quality, education, and leadership. From 179 initial records, 24 articles were selected through screening, eligibility assessment, and thematic relevance analysis. The findings reveal that AI contributes to educational quality through personalized learning, adaptive assessment, learning analytics, digital mentorship, improved academic services, and data-informed decision-making. The review further indicates that the successful implementation of AI and digital transformation depends on institutional readiness, digital leadership, governance structures, teacher competence, quality assurance systems, and ethical oversight. The study highlights that educational quality should not be measured solely by technological efficiency or academic performance. For Islamic education, quality management should also incorporate moral development, religious literacy, proper ethical conduct, trustworthiness, justice, honesty, spiritual growth, and human-centered pedagogy. The findings provide a conceptual framework for integrating AI-driven quality management with value-based educational principles and offer guidance for future research and institutional policy development.